IDENTIFICATION THE EFFECT OF THE EXISTENCE OF CAMPUS INSTITUT TEKNOLOGI SUMATERA IN THE LAND USE CHANGES AND PRICES IN THE SURROUNDING AREA - Isye Susana Nurhasanah; Oriestha Dwitrika; Citra Persada (Journal of Science and Applicative Technology, 2018)
This research identifies the presence of Institut Teknologi Sumatera in altering the land use of the surrounding area. The very rapidly changes around the campus ITERA is altering the land use at present. It is because of the need for the land in order to meet the needs of ITERA’s students who come from outside the regions. These needs can be seen in the form of land use changes from agriculture, plantation, and vacant land into rented house, food stalls, and photocopy services as a provider of facilities for students ITERA. The data were collected through questionnaires, as well as interviews with stakeholders and community members in the ITERA campus’ neighborhood. The analytical method adopted in this research is geographic information systems to describe a changes in altering the land use and prices. In addition this research explain how the alter land use are happening. The findings suggest that the presence of Institut Teknologi Sumatera, to some degree, has influenced how the land is being managed in the surrounding area and the price of the land.